ANALYSIS FRAME OF HUSKER MACHINE TYPE LM-24 USING SOLIDWORKS SOFTWARE 2018 - Ariyanto; Tati Noviati (Asosiasi Dosen Muda Indonesia, 2022)
Rice is a strategic commodity that directly affects the lives of the majority of the Indonesian population, therefore the program to increase rice production gets a top priority from the government to achieve food security and farmers' welfare. The work of farmers in order to increase domestic rice production, for example is the Rice Milling Unit (RMU). The technology that is usually used in producing grain into rice, one of which is a husker (husker) machine. grains of rice, in the rice mill there is a husker machine weighing 115 kg which is only based on the floor so the machine requires a support or foundation so as not to cause vibrations that can damage the structure of the building around it, therefore it is necessary to make a design the support frame is sturdy and also flexible. To determine the strength of the frame, it is necessary to analyze the calculation of the frame simulation which includes the simulation of Von misses, Displacement and Safety factor, the simulation is carried out at a load of 1127 N which produces a Von misses max value of 102,486 MPa, with the highest displacement value of 0.274 mm and the lowest value of 0. mm, and produces a safety factor value of 2,439. with the value of the safety factor, it can be said that the frame construction is safe.